An Experimental Study of the Flexural Bearing Capacity of Reinforced Concrete Beams Damaged by Explosions Using Piezoelectric Smart Aggregates - Kai Xu; Shilong Sheng; Ronghui Jiang; Qian Feng (Sensors)
Two identically sized RC beams were fabricated to investigate the effects of explosive loads on the flexural behaviour of Reinforced Concrete (RC) beams. One of the beams was subjected to an explosive load to induce post-explosion damage, and subsequently, both beams underwent flexural capacity testing. Integrating piezoelectric smart aggregates (SAas) within the beams facilitated continuous observation of the damage conditions, allowing for the assessment of internal concrete deterioration from explosive impacts to bending failures. The internal crack development index R was established using the Wavelet Packet Energy Analysis method. Combined with the structure’s residual capacity-based damage assessment criterion, the relationship between R and component damage was found. This allowed us to identify the change in the bending capacity of RC beams after explosion damage and the quantitative damage assessment of the beam to be realised, providing valuable insights for structural engineers and researchers. Comparing the flexural test results between the explosively pre-damaged beam and the undamaged test beam, it was observed that the neutral axis of the damaged beam was significantly elevated, accompanied by a notable reduction in flexural capacity. By examining the variation curve of the internal crack development index R, it was noted that during the initial stage of the bending flexural test, due to bending deformation, cracks in the core region of the pre-damaged beam gradually healed, leading to a pseudo-decrease in the damage index. After reaching a minimum point, the damage progressed faster until failure occurred.